2019
DOI: 10.1074/jbc.ra119.009162
|View full text |Cite
|
Sign up to set email alerts
|

Cx43 phosphorylation–mediated effects on ERK and Akt protect against ischemia reperfusion injury and alter the stability of the stress-inducible protein NDRG1

Abstract: Edited by Alex Toker Gap junctions contain intercellular channels that enable intercellular communication of small molecules while also serving as a signaling scaffold. Connexins, the proteins that form gap junctions in vertebrates, are highly regulated and typically have short (<2 h) half-lives. Connexin43 (Cx43), the predominate connexin in the myocardium and epithelial tissues, is phosphorylated on more than a dozen serine residues and interacts with a variety of protein kinases. These interactions regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 62 publications
8
25
1
Order By: Relevance
“…The analysis of the amount of Cx43 in this strain in vascular smooth muscle cells did not demonstrate reduced levels of Cx43, which may be due to the different tissue/cell types analyzed [ 34 ]. In Cx43 PKCmut and Cx43 CK1mut mice, we found a similar decrease of Cx43 in mouse hearts as previously published [ 30 , 54 , 70 ]. Whereas others suggested that the decreased Cx43 protein levels in Cx43 CK1mut mice are due to posttranscriptional alterations [ 70 ], the reason for the reduced Cx43 protein amount in Cx43 MAPKmut , Cx43 PKCmut , and Cx43 CK1mut mice remains unclear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The analysis of the amount of Cx43 in this strain in vascular smooth muscle cells did not demonstrate reduced levels of Cx43, which may be due to the different tissue/cell types analyzed [ 34 ]. In Cx43 PKCmut and Cx43 CK1mut mice, we found a similar decrease of Cx43 in mouse hearts as previously published [ 30 , 54 , 70 ]. Whereas others suggested that the decreased Cx43 protein levels in Cx43 CK1mut mice are due to posttranscriptional alterations [ 70 ], the reason for the reduced Cx43 protein amount in Cx43 MAPKmut , Cx43 PKCmut , and Cx43 CK1mut mice remains unclear.…”
Section: Discussionsupporting
confidence: 90%
“…However, the similar infarct sizes following I/R we observed in all strains analyzed argue against an influence of Cx43 phosphorylation at MAPK, PKC, or CK1 target sites on myocardial I/R injury per se. Similar infarct sizes in WT and Cx43 CK1mut mice have already been demonstrated after myocardial I/R in animals less than 1 year old [70]. However, it must be considered that in the analyzed mouse strains-especially in Cx43 PKCmut mice-not only the phosphorylation of Cx43 but also the total amount of the protein is reduced.…”
Section: Cx43supporting
confidence: 63%
“…Cx43 CK1 mice develop deleterious cardiac phenotypes (Remo et al, 2011) and differ in their response to ischemia reperfusion injury (Solan et al, 2019) owing to alterations in cardiac gap junction formation and function, lending support to the importance of these phosphorylation sites during the injury response. In the latter case, increased phosphorylation of Cx43 at MAPK sites S262, S279 and S282 was observed in cardiac tissue in the Cx43 CK1 mice (Solan et al, 2019). Interestingly, Cx43 MAPK mice closed wounds ∼20% faster than Cx43 WT .…”
Section: Resultsmentioning
confidence: 94%
“…For example, in the normal mouse heart, Cx43 is heavily phosphorylated at CK1 sites, but upon ischemia, these sites rapidly become dephosphorylated followed by gap junction disassembly (Axelsen et al, 2006;Lampe et al, 2006). Cx43 CK1 mice develop deleterious cardiac phenotypes (Remo et al, 2011) and differ in their response to ischemia reperfusion injury (Solan et al, 2019) owing to alterations in cardiac gap junction formation and function, lending support to the importance of these phosphorylation sites during the injury response. In the latter case, increased phosphorylation of Cx43 at MAPK sites S262, S279 and S282 was observed in cardiac tissue in the Cx43 CK1 mice (Solan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…ERK1/2 is involved in the reperfusion injury salvage kinase (RISK) pathway, which confers cardioprotection when activated (32,33). The activation of ERK1/2 signaling protects the heart from ischemia reperfusion injury (34,35). However, in aging hearts, the activation of ERK1/2 is compromised, which leads to the impairment of cardiac tolerance to ischemia.…”
Section: Discussionmentioning
confidence: 99%